2016
DOI: 10.18006/2016.4(5).475.483
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield response of sweet potato to different tillage methods and phosphorus fertilizer rates in Ghana

Abstract: A field experiment was conducted during the major cropping season of 2014 at the Plantation Section of the Department of Crop and Soil Sciences, Kwame Nkrumah University of Science and Technology, Ghana to evaluate the effect of tillage and different application rates of phosphorus fertilizer on the growth and yield of sweet potato variety Okumkom. The tillage methods are ridge & mound while the different rates of phosphorus fertilizers are 0, 30, 60, 90 and 120 kg P2O5/ha in triple superphosphate (46% P2O5) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 9 publications
7
13
0
1
Order By: Relevance
“…The average yield increment in CA (15.9 t ha −1 ) for sweet potato in Yemu was statistically significant compared to CT (10.1 t ha −1 ). The result is consistent with Dumbuya et al [66] sweet potato yield findings for the tilled system (9.5 to 15.8 t ha −1 ) in southern Ghana. On the other hand, garlic and onion yields in Dangishita and Robit sites were generally small, however, the yield increment in CA was statistically significant (α = 0.05).…”
Section: Effects Of Conservation Agriculture On Irrigation Water Prodsupporting
confidence: 92%
“…The average yield increment in CA (15.9 t ha −1 ) for sweet potato in Yemu was statistically significant compared to CT (10.1 t ha −1 ). The result is consistent with Dumbuya et al [66] sweet potato yield findings for the tilled system (9.5 to 15.8 t ha −1 ) in southern Ghana. On the other hand, garlic and onion yields in Dangishita and Robit sites were generally small, however, the yield increment in CA was statistically significant (α = 0.05).…”
Section: Effects Of Conservation Agriculture On Irrigation Water Prodsupporting
confidence: 92%
“…Planting pattern 3 had the highest number of branches per plant at day 75 (4.7 branches), followed by pattern 2 (3.4). Dumbuya et al (2016) reported that sweet potato had 4.20 and 5.97 branches per plant at 30 and 60 days after planting. Ogbe et al 2012reported branch number per plant of 11 cultivars ranged from 3.83 to 4.83 which is similar to our results.…”
Section: Rainy Seasonmentioning
confidence: 99%
“…Pattern 5 gave the highest number of tubers /plant and number of tubers/ha (7.7 and 408.9x10 3 tubers, respectively) ( Table 1). Dumbuya et al (2016) studied the response of phosphorus rates on growth and yield of sweet potato cv. Okumkom and their results showed that the number of marketable roots per plant ranged from 3.20 to 4.63 which is much lower than our study.…”
Section: Rainy Seasonmentioning
confidence: 99%
“…A combination between superphosphate at the recommended P level and VAM-fungi inoculation treatment was found to significant increase sweet potato root production and quality [9]. In investigating the effect of tillage methods and phosphorus fertilizer on growth and yield response of sweet potato, results showed that plant growth was not significantly affected by tillage but highest growth and yield was observed from phosphorus treatment [10]. Poultry manure and NPK fertilizers had a significant effect on the yield of sweet potatoes [11].…”
Section: Introductionmentioning
confidence: 99%